CRISPR/dCas9‐Mediated Multiplex Gene Repression in Streptomyces. Issue 9 (4th July 2018) - Zhao, Yawei; Li, Lei; Zheng, Guosong; Jiang, Weihong; Deng, Zixin; Wang, Zhijun; Lu, Yinhua
Abstract : Streptomycetes are Gram‐positive bacteria with the capacity to produce copious bioactive secondary metabolites, which are the main source of medically and industrially relevant drugs. However, genetic manipulation of Streptomyces strains is much more difficult than other model microorganisms like Escherichia coli and Saccharomyces cerevisiae . Recently, CRISPR/Cas9 or dCas9‐mediated genetic manipulation tools have been developed and facilitated Streptomyces genome editing. However, till now, CRISPR/dCas9‐based interference system (CRISPRi) is only designed to repress single gene expression. Herein, the authors developed a novel CRISPRi system for multiplex gene repression in the model strain Streptomyces coelicolor . In this system, the integrative plasmid pSET152 is used as the backbone for the expression of the dCas9/sgRNA complex and both dCas9 and sgRNAs are designed to be under the control of constitutive promoters. Using the integrative CRISPRi system, the authors achieved efficient repression of multiple genes simultaneously; the mRNA levels of four targets are reduced to 2–32% of the control. Furthermore, it is successfully employed for functional gene screening, and an orphan response regulator (RR) (encoded by SCO2013 ) containing an RNA‐binding ANTAR domain is identified being involved in bacterial growth. Collectively, this integrative CRISPRi system is very effective for multiplex gene repression in S. coelicolor, which could be extended to other Streptomyces strains for functional gene screening as well as for metabolic engineering. Abstract : Genetic manipulation of Streptomyces strains is much more difficult than other model microorganisms like Escherichia coli and Saccharomyces cerevisiae . In this study, the authors developed an integrative CRISPRi system for efficient multiplex gene repression in the model strain Streptomyces coelicolor, which will greatly facilitate functional gene screening as well as metabolic engineering in Streptomyces .